The Cooperation of Russia and China in Central Asia - A. Lukin (Международная аналитика)
The article analyses the process of Sino-Russian rapprochement which has significantly intensified since the worsening of Russia’s relations with the West in 2014. This process is studied as a part of the emerging of Greater Eurasia in place of Greater Europe which was envisioned in late 1980s. The states of Greater Eurasia, will not be tied by alliance relations, as are the United States and its European satellites. Some of them may turn to different centers of power; however, on the whole, they will form a unity, brought together by core interests. Precisely, this kind of democratic unity of Greater Europe could not be established by the United States and its allies. Attempting to subordinate every state to their dictates, they have united allies from most of Eastern Europe but lost Russia and Central Asia, and are increasingly antagonizing China and India, forcing them to draw closer to each other even in spite of significant contradictions. Only the future will tell who will succeed and who will not.